Gambaran Pengetahuan Ibu Hamil Dan Ibu Balita Tentang Status Stunting Di Posyandu Kelurahan Banjarmlati Kota Kediri - Budiretanani, Dwi Ari; Utami, Budhi; Herawati, Elysabet; Astuti, Puji; Gunawan, Hanif Widi (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2023)
The distribution of stunting cases in Kediri City is dominated by the Kota District area. The Kediri city government continues to strive to reduce the stunting rate with various programs to accelerate stunting reduction, one of which is education and health education. This activity aims to provide information and knowledge to pregnant women and mothers of toddlers in the Banjarmlati sub-district, Kediri City about stunting and to determine the level of understanding of pregnant women and mothers of toddlers regarding nutritional needs and stunting. The method used is health education with lectures and interactive methods, which ends with giving a post-test. The post-test results showed the highest correct answer score was 83.4% regarding stunting knowledge in general; 95.8% about efforts to prevent stunting; and 91.7% about the impact of stunting on children's subsequent growth and development. Based on the results above, the knowledge of the mothers who participated in the counseling after being given the material was considered very good so that the health education carried out was considered successful.